Human Rights and Constitutional Supremacy in Indonesia: Normative Guarantees and Policy Disharmony in Natural Resource Management, Freedom of Expression, and Public Participation - Moh. Sigit Gunawan; Siska Karina (Politeknik Siber Cerdika Internasional, 2026)
Background: The research is grounded in the post-amendment strengthening of human rights guarantees following the amendments to the 1945 Constitution of the Republic of Indonesia (1999–2002), which marked a paradigmatic shift from governmental supremacy toward constitutional supremacy. Objective: This study aims to analyze the constitutional status of human rights within the framework of Indonesian constitutional law and to examine the disharmony between constitutional supremacy and the practice of public policymaking. Methods: The research employs a normative juridical method, utilizing statutory, conceptual, and analytical approaches to constitutional provisions, legal doctrines, and constitutional court decisions. Results: The findings indicate that, at the normative level, human rights have attained a reinforced position as constitutional rights binding upon all branches of state power. Nevertheless, in the realm of public policy implementation, tensions persist between administrative legality and constitutional legitimacy, particularly in matters concerning development policies, freedom of expression, and public participation. Conclusion: The study concludes that the effective protection of human rights is contingent upon the integration of constitutional supremacy in its normative, institutional, and ethical dimensions, thereby ensuring that the Constitution operates as an instrument of substantive justice within a democratic rule-of-law state.